N, B-codoped defect-rich graphitic carbon nanocages as high performance multifunctional electrocatalysts. (December 2017) - Lu, Ziyang; Wang, Jing; Huang, Shifei; Hou, Yanglong; Li, Yanguang; Zhao, Yueping; Mu, Shichun; Zhang, Jiujun; Zhao, Yufeng
Abstract: Nanocarbon materials recognized as effective and inexpensive catalysts for independent electrochemical reactions, are anticipated to possess a broader spectrum of multifunctionality toward oxygen reduction reaction (ORR), oxygen evolution reaction (OER), and hydrogen evolution reaction (HER). A rational design of trifunctional nanocarbon catalyst requires balancing the heteroatoms-doping and defect-engineering to afford desired active centers and satisfied electric conductivity, which however is conceptually challenging while desires in-depth research both experimentally and theoretically. This work reports a N, B-codoped graphitic carbon nanocage (NB-CN) with graphitic yet defect-rich characteristic as a promising trifunctional electrocatalyst through a facile thermal pyrolysis assisted in-situ catalytic graphitization (TPCG) process. Density functional theory (DFT) calculations are conducted, for the first time, to demonstrate that the best performance for ORR/OER and HER can be originated from the configuration with B meta to a pyridinic-N, which presents a minimum theoretical overpotential of 0.34 V for ORR, 0.39 V for OER, and a lowest Gibbs free-energy (ΔGads ) of 0.013 eV for HER. A primary zinc-air battery is assembled presenting a maximum power density of 320 mW cm −2 along with excellent operation durability, evidencing great potential in practical applications. Graphical abstract: The N, B-codoped defect-rich graphitic carbon nanocages (NB-CN) are prepared through a technique of in situ vapor deposition. The NB-CN exhibits efficient multifunctional catalytic activity for ORR, OER and HER, shows potential practical performances in the fields of metal-air battery, fuel cell and water splitting. Highlights: A N, B-codoped carbon nanocage is reported for high efficiency multifunctional electrocatalyst. DFT calculations reveal the catalytic compatibility of the N, B-codoping for ORR/OER/HER. A primary zinc-air battery is assembled presenting a maximum power density of 320 mW cm −2 .